2007
DOI: 10.1111/j.1439-0426.2007.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of laboratory studies to develop a dispersal model for Missouri River pallid sturgeon early life intervals

Abstract: Summary Understanding the drift dynamics of pallid sturgeon (Scaphirhynchus albus) early life intervals is critical to evaluating damming effects on sturgeons. However, studying dispersal behavior is difficult in rivers. In stream tanks, we studied the effect of velocity on dispersal and holding ability, estimated swimming height, and used the data to estimate drift distance of pallid sturgeon. Dispersal was by days 0–10 embryos until fish developed into larvae on day 11 after 200 CTU (daily cumulative tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(98 citation statements)
references
References 7 publications
5
92
1
Order By: Relevance
“…82 position after settling and then swim upstream in order to enter a chute. Laboratory studies indicated that recently settled age-0 sturgeon (Kynard et al 2007), as well as individuals up to 75 mm total length (D. Deslauriers, South Dakota State University, unpublished data), may have difficulty holding position in water velocities that are relatively slow within the LMOR (e.g., 0.3 m/s). Furthermore, even if exogenously feeding sturgeon can hold position, these fish may experience a velocity barrier preventing them from swimming upstream into the chute as currents can be turbulent and swift at downstream chute outlets, particularly during higher water levels that are common during the free-embryo drift period.…”
Section: Discussionmentioning
confidence: 99%
“…82 position after settling and then swim upstream in order to enter a chute. Laboratory studies indicated that recently settled age-0 sturgeon (Kynard et al 2007), as well as individuals up to 75 mm total length (D. Deslauriers, South Dakota State University, unpublished data), may have difficulty holding position in water velocities that are relatively slow within the LMOR (e.g., 0.3 m/s). Furthermore, even if exogenously feeding sturgeon can hold position, these fish may experience a velocity barrier preventing them from swimming upstream into the chute as currents can be turbulent and swift at downstream chute outlets, particularly during higher water levels that are common during the free-embryo drift period.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the larvae of long migratory, potamodromous sturgeon species feature a continuous drift over several days and hundreds of kilometres (see Online Resource). Drift distance and duration are highly variable among species, and may be genetically coded in order to reach distinct nursery habitats and to compensate for the long upstream migrations of the adults (D'Amours et al 2001;Kynard and Horgan 2002;Kynard et al 2007aKynard et al , 2007bBraaten et al 2008Braaten et al , 2012. Instead of a continuous downstream movement, the early dispersal of other potamodromous species potentially includes a sequence of drifting phases (primarily during night), interspersed with periods of inshore settlement in nursery habitats (primarily during day) (Carter et al 1986;Gadomski and Barfoot 1998).…”
Section: What Types Of Fishes Drift?mentioning
confidence: 99%
“…Flume experiments have a great potential to reveal specific peculiarities of the drift mode, however, they are rarely applied (Persat and Olivier 1995;Kynard et al 2007a;Kaminskas 2011;Pavlov et al 2011;Zens 2015). We suggest that future work should focus on the transport mode of different species (e.g.…”
Section: An Integrated Approach To the Drift Of Early Life Stages Of mentioning
confidence: 99%
See 2 more Smart Citations